Reconfiguring Tarbiyah for the Market: Subject-Making of Pious and Prosperous Muslims in Digital Pesantren - Alvin Nugraha Kusuma Satya (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This article examines the marketisation of alternative Islamic education in Indonesia through an ethnographic study of Pondok An-Najah, a ‘Digital Islamic Boarding School’ in Yogyakarta. I argue that Pondok An-Najah exemplifies how market forces are reshaping Islamic educational institutions. Marketisation operates at two interconnected analytical levels. First, at the institutional level, neoliberalisation has transformed Islamic educational institutions, particularly in the case of Pondok An-Najah, into hybrid entities, functioning both as a religious educational institution and a sharia outsourcing company that manages santri as productive workers. Second, at the individual level, consumerisation becomes a mode of subject-making, as santri actively consume the institution's ‘free education’ and ‘work relationship networks’ to shape themselves into ‘Muslim Winners’—a subjectivity combining Islamic piety with entrepreneurial aspirations. This reconfigures tarbiyah into a technology of the self that aligns santri aspirations with market ideas and ideals. However, this self-formation comes at a cost: to succeed in this internal market, santri must navigate the debt financing behind ‘free education’ and vulnerable patronage relations, which blur the boundaries between religious devotion and economic value extraction in the digital economy